Team diversity, conflict, and trust: Evidence from the health sector - Nawaz, Muhammad Rafay; Ishaq, Muhammad Ishtiaq; Ahmad, Rehan; Faisal, Muhammad; Raza, Ali (Frontiers in Psychology, 2022)
The current study aims to determine the impact of diversity and intra-team trust on the conflict in the health sector of Pakistan. This study also measures the moderating role of trust in the relationship between diversity and conflict among team members. Data was collected using personally administered questionnaires from 61 teams, including 377 respondents working in four public sector hospitals in Pakistan, which were selected using simple random sampling technique. The results revealed that diversity (as a composite) positively influences task conflict, while its two components – surface-level diversity and deep-level diversity – are associated positively with task conflict. Moreover, the results also lead to an exciting finding that trust among team members could reduce the positive influence of diversity on team members' conflict. The implications for theory and practitioners are presented along with the avenues for future research directions.